DETERMINATION OF ADOLESCENT WORLDVIEW - COMBATING NEGATIVE INFLUENCE OF SOCIAL MEDIA - Rose Emmaria Tarigan (Ikatan Sarjana Komunikasi Indonesia, 2017)
Use of social media creates positive or negative impacts on adolescents. There are a number of factors enabling adolescents to make use of social media positively. One of the factors studied in this research is the adolescent worldview. The adolescent worldview greatly determines the way she behaves and her attitude towards social media. The result of this research shows that adolescent worldview may release and enables her to reject negative impacts of social media, particularly from modern culturalisms as relativism, individualism, emotionalism, presentism (present-time ism), materialism, autonomy, victimism, and turn it into a positive impact on herself. Worldviews may be differentiated based on three categories namely religion, spirituality and secularity. This research is conducted by explorative-qualitative approach, using case study research method. Data collection process was conducted by in-depth interview with late adolescents.